Becoming a professional counselor : preparing for certification and comprehensive exams - Wallace, Sheri A.; Lewis, Michael D. (Thousand Oaks, Calif. : Sage, 1998)
Now in its 2nd edition, Becoming a Professional Counselor brings up to date the names of key organisations and introduces new information relevant to changes in the counsellor certification examination.
Includes bibliographical references.
Keywords: Counseling; Counseling -- Examinations -- Study guides; Counselors -- Certification -- United States